Computational fluid dynamics prediction of formaldehyde emission and sorption processes in a small test chamber with mixing fan and vents. (15th May 2020) - Mu, Yu-Tong; Li, Zi-Ai; Gu, Zhao-Lin; Tao, Wen-Quan
Abstract: Characterizing the emission performance of formaldehyde is critical for control strategies. Most previous emission models assume that formaldehyde concentrations are well-mixed. In this study, a computational fluid dynamics-based model is developed for simulating the mass transfer and adsorption/desorption processes of formaldehyde from particleboards in a chamber with a mixing fan. Numerical investigations on the impacts of the mixing fan, adsorption/desorption rate constants, and key transport parameters influencing the emission behaviors are conducted for the first time. The results show that the complete mixing assumption is not appropriate in the early emission period. Incomplete mixing becomes more significant with a decreasing rotation speed, leading to a time-dependent equivalent mass transfer coefficient. The deviation in the maximum concentration between the simulated curves with and without the adsorption/desorption effect is approximately 8.5%. A coefficient of mixing of 0.0283 is suitable for evaluating complete mixing in the chamber. With an increase in the rotation speed, the degree of mixing improves, and the mass transfer coefficient increases sub-linearly. Secondary reemission becomes more significant and begins earlier for materials with lower partition coefficients and higher diffusivity. Highlights: A 3D model considering the whole transport processes of formaldehyde is proposed. Impact of the fan on the mixing degree and mass transfer coefficient is revealed. Incomplete mixing in the early period governed by circulation current is observed. Emission profiles are sensitive to the degree of mixing and the ventilation rate. The adsorption/desorption behaviors are affected by the key transport parameters.